Book art studio handbook : techniques and methods for binding books, creating albums, making boxes and more - Dolin, Stacie (Quarry Books, 2013)
"As the "book" morphs and evolves into a malleable, digital file, interest in the classic form is reignited in book lovers and crafters. The Book Art Studio Handbook offers readers a comprehensive and accessible guide to not only the nuts and bolts of this classic art, but insight into the artisan's lifestyle. This book goes beyond quick craft projects and into the heart of bookmaking, binding, letterpress printing, decorative cover techniques, book conservation, and other book arts. It is an essential companion book for all paper lovers and bibliophiles--especially as the book as object becomes more prominent a concept"--Provided by publisher